The rebels of Ireland : [large type] : the Dublin saga - Rutherfurd, Edward (Random House Large Print, 2006)
Once again Rutherfurd takes us inside the process of history by tracing the lives of several Dublin families from all strata of society, Protestant and Catholic, rich and poor, conniving and heroic.